An analysis of sports ethics from a radical behavioristic standpoint (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The objective of this work was to analyze sports ethics from B.F. Skinner’s Radical Behaviorism standpoint. Thus, the sports context was characterized and as well as how sports ethics is understood traditionally. Next, the Skinnerian description of how we value good/bad, moral/immoral, ethical/unethical things is presented. Then, the sports context was analyzed based on the concepts analyzed, discussing the importance of the fair play notion. Value judgements are based on reinforcement effects and on selective contingencies satisfaction. Sports have formally established rules for “legal” and “illegal” conducts, codes of conduct and informal values that classify behavior into sporting and non-sporting. Sportsmanship or fair play involves not only prudence (playing according to the rules) but also problem-solving and decision-making behaviors before situations that generate conflict of consequences for individuals, groups or cultures.
Keywords: fair play; sportsmanship; radical behaviorism; moral behavior